Influence of dietary protein and energy levels on sow backfat thickness - Surasak Jittakhot (2016)
The objective of the present study was to determine the influences of dietary protein and energy levels on sow backfat thickness. The study was conducted by randomly measured backfat thickness in both pregnant and lactating stages of 10,401 sows from 7 commercial herds in Thailand. The pregnant sow diets contained 14.4% crude protein (CP) and 3,346 kcal metabolizable energy (ME)/kg. The lactating sow diet contained 18.8% CP and 3,660 kcal ME/kg. The percentage of dietary protein was positively correlated with backfat thickness (r = 0.036, P < 0.01) and the metabolizable energy of the diet was positively correlated (r = 0.053, P < 0.01). Upon, stepwise method of multiple linear regression analysis showed that the percentage of dietary crude fat (X, %) was a key factor affecting the thickness of sow backfat (Y, mm) with statistical significance. The regression equation was; Y = 14.4 + (0.2X), (R2 = 0.009, P < 0.01). Conclusion, a major nutritional factor that response for changing of sow backfat thickness was the dietary energy in sow diet.